2022
DOI: 10.1007/s12243-022-00914-x
|View full text |Cite
|
Sign up to set email alerts
|

Digital sufficiency: conceptual considerations for ICTs on a finite planet

Abstract: ICT hold significant potential to increase resource and energy efficiencies and contribute to a circular economy. Yet unresolved is whether the aggregated net effect of ICT overall mitigates or aggravates environmental burdens. While the savings potentials have been explored, drivers that prevent these and possible counter measures have not been researched thoroughly. The concept digital sufficiency constitutes a basis to understand how ICT can become part of the essential environmental transformation. Digital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 128 publications
0
20
0
Order By: Relevance
“…Considering the medium-term perspective, specifically until around 2030, the ICT industry represents a rapidly growing sector that will significantly contribute to addressing environmental challenges such as CO2 emissions, raw material consumption and pollution, among others. The literature highlights rebound effects and the need for sufficiency policies to complement consistency and efficiency efforts in the ICT sector (e.g., Santarius et al 2022). While the latter are not yet widespread, sufficiency policies are still in their infancy or even taboo, as we were able to observe in the field.…”
Section: Introductionmentioning
confidence: 57%
“…Considering the medium-term perspective, specifically until around 2030, the ICT industry represents a rapidly growing sector that will significantly contribute to addressing environmental challenges such as CO2 emissions, raw material consumption and pollution, among others. The literature highlights rebound effects and the need for sufficiency policies to complement consistency and efficiency efforts in the ICT sector (e.g., Santarius et al 2022). While the latter are not yet widespread, sufficiency policies are still in their infancy or even taboo, as we were able to observe in the field.…”
Section: Introductionmentioning
confidence: 57%
“…The study findings have revealed that the ICT investment is crucial for facilitating and encouraging the adoption of renewable energy, which is supported by the existing literature [ 44 , 45 , 48 , 50 , 54 , 116 , 117 ]. The study of Wang, Qamruzzaman [ 8 ], Qamruzzaman and Kler [ 18 ], Su, Wang [ 47 ], Santarius, Bieser [ 49 ] revealed that ICT is crucial in seamlessly incorporating renewable energy sources into the current energy infrastructure; additionally, it empowers consumers by providing them with the necessary information to make well-informed and environmentally conscious energy decisions [ 45 ]. ICT facilitates the implementation of advanced smart metering systems, which offer instantaneous information regarding energy usage.…”
Section: Discussion Of the Study Findingsmentioning
confidence: 99%
“…As sufficiency provides a fundamentally different approach to living compared to the growth and efficiency-oriented society of the past 250 years, the research field is multi-and inter-disciplinary, ranging from economics and marketing (Gossen et al, 2019;Kropfeld and Reichel, 2021;Bocken et al, 2022) to political sciences (Spangenberg and Lorek, 2019) and environmental modeling (Speck and Hasselkuss, 2015), to name but a few. See also Santarius et al (2022) for a truly multi-disciplinary approach to addressing digital sufficiency.…”
Section: Su Ciencymentioning
confidence: 99%